THE IMPACT OF LIMITED PHYSICAL ACTIVITY ON THE BODY OF YOUNG PEOPLE - Czarnecki, D.; Skalski, D. W.; Tsyhanovska, N. V.; Svyshch, L.; Kyryk, O. (Rehabilitation and Recreation, 2023)
Among the most important factors that have a significant impact on health and life expectancy, physical activity should be mentioned. Physical activity is one of the main components of a healthy lifestyle. There is a common belief that physical activity is one of the most important categories determining the proper functioning of the human body. Leading an active lifestyle has many benefits. The benefits of taking up physical activity are obvious. Systematic physical activity is a very strong biological stimulator and is one of the main determinants of human physical and mental health. Regular physical activity determines the quality and length of human life. Properly selected activity also enriches the intellectual sphere and allows you to maintain a balance between the condition of the body and the state of mind. Physical activity contributes to a better psychophysical condition, as well as feeling better. Nevertheless, in the general issue of physical activity, the concept of physical fitness is also important, which defines and determines whether a person is capable of undertaking any activity that includes movement components.